Degenerated nucleus pulposus cells derived exosome carrying miR-27a-3p aggravates intervertebral disc degeneration by inducing M1 polarization of macrophages - Xin Zhao; Zhen Sun; Benchi Xu; Wei Duan; Le Chang; Kangwei Lai; Zhengxu Ye (Journal of Nanobiotechnology, 2023)
Abstract Background Intervertebral disc degeneration (IVDD) is a major contributor to spinal disorders. Previous studies have indicated that the infiltration of immunocytes, specifically macrophages, plays a crucial role in the advancement of IVDD. Exosomes (exo) are believed to play a significant role in intercellular communication. This study aims to investigate the role of exosomes derived from degenerated nucleus pulposus (dNPc) in the process of macrophages M1 polarization. Methods Nucleus pulposus (NP) tissue and nucleus pulposus cells (NPc) were collected from patients with intervertebral disc degeneration (IVDD) and idiopathic scoliosis. Immunohistochemistry analysis was performed to determine the number of M1 macrophages in NP tissue. Subsequently, exosomes derived from degenerated NP cells (dNPc-exo) and non-degenerated NP cells (nNPc-exo) were collected and co-cultured with M0 macrophages, which were induced from THP-1 cells. The M1 phenotype was assessed using western blot, flow cytometry, immunofluorescence staining, and qRT-PCR. RNA-sequencing analysis was conducted to examine the expression levels of microRNAs in the dNPc-exo and nNPc-exo groups, and qRT-PCR was performed to investigate the effect pf different microRNA to induce macrophage polarization. Furthermore, western blot and qRT-PCR were employed to demonstrate the regulatory effect of microRNAs carried by dNPc-exo on downstream target signaling pathways in macrophages. Finally, an animal model of IVDD was utilized to investigate the impact of dNPc-exo on inducing M1 polarization of macrophages and its role in the IVDD process. Results In this study, we observed an increase in the number of M1 macrophages as the intervertebral disc (IVD) degraded. Additionally, we discovered that dNPc releases exosomes (dNPc-exo) could promote the polarization of macrophages towards the M1 phenotype. Notably, through RNA-sequencing analysis of dNPc-exo and nNPc-exo groups, we identified miR-27a-3p as a highly expressed miRNA in the dNPc-exo group, which significantly influences the induction of M1 polarization of macrophages. And then, we discovered that dNPc-exo has the ability to transport miR-27a-3p and target the PPARγ/NFκB/PI3K/AKT signaling pathway, thereby influencing the M1 polarization of macrophages. We conducted experiments using rat model of IVDD and observed that the exosomes carrying miR-27a-3p actually induced the M1 polarization of macrophages and exacerbated the degradation of IVD. Conclusion In conclusion, our findings highlight the significant role of dNPc-exo in IVDD process and provide a basis for further investigation into the mechanism of IVDD and the potential of exosome-based therapy. Graphic abstract